2017
DOI: 10.1002/cne.24217
|View full text |Cite
|
Sign up to set email alerts
|

Afferent and efferent connections of the interpeduncular nucleus with special reference to circuits involving the habenula and raphe nuclei

Abstract: The habenula is an epithalamic structure differentiated into two nuclear complexes, medial (MHb) and lateral habenula (LHb). Recently, MHb together with its primary target, the interpeduncular nucleus (IP), have been identified as major players in mediating the aversive effects of nicotine. However, structures downstream of the MHb-IP axis, including the median (MnR) and caudal dorsal raphe nucleus (DRC), may contribute to the behavioral effects of nicotine. The afferent and efferent connections of the IP have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 164 publications
(367 reference statements)
6
71
0
1
Order By: Relevance
“…In addition, mPOA MCH neurones did not colocalise with VGLUT2 cell bodies, a well‐established marker of glutamatergic neurones in the hypothalamus (Figure B). VGLUT3‐expressing cell bodies can be observed in several brain regions, particularly in the brainstem . In the preoptic area, VGLUT3 expression was basically restricted to axon terminals, many of them making apparent contacts with MCH neurones (Figure C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, mPOA MCH neurones did not colocalise with VGLUT2 cell bodies, a well‐established marker of glutamatergic neurones in the hypothalamus (Figure B). VGLUT3‐expressing cell bodies can be observed in several brain regions, particularly in the brainstem . In the preoptic area, VGLUT3 expression was basically restricted to axon terminals, many of them making apparent contacts with MCH neurones (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…VGLUT1 was not studied because this transporter is poorly expressed in the hypothalamus; however, we cannot rule out the possibilty that VGLUT1 mediates glutamate release in mPOA MCH neurones. Additionally, VGLUT3 antibody labels predominantly synaptic terminals in the hypothalamus, although cell bodies can be observed in the paraventricular nucleus of the hypothalamus (J. Donato, unpublished data) and in the brainstem …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, insofar as MHb fibers pass through LHb enroute to the fr and passing axons and terminal fields are poorly differentiated by anterograde tracing with audioradiography, the question had remained open. Recently, however, Lima et al (2017) have provided tracing evidence for reciprocal connections between MHb and LHbM (but see Kim and Chang, 2005). Similarly, Kim (2009) has demonstrated convincingly with complementary retrograde and anterograde tract tracing that homologous parts of the LHb on the two sides of the midline are robustly related by reciprocal connections.…”
Section: Afferent Connectionsmentioning
confidence: 99%
“…More specifically, the MHb may play a larger role in adaptive behaviors, where mounting evidence has demonstrated that loss of vMHb function leads to deficits in fear extinction and escape behaviors. Nevertheless, while the circuitry and cellular composition of the MHb has been well-characterized, the endogenous functions of the MHb remain relatively unknown and have recently become the focus of addiction neuroscience (Qin & Luo 2009;Aizawa et al 2012;Lima et al 2017).…”
Section: Introductionmentioning
confidence: 99%